Pengaruh Penyuluhan terhadap Pengetahuan Kesehatan Reproduksi Remaja - khoirul anam; Dewi Rakhmawati (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
iKnowledge iof ireproductive ihealth iis iindispensable ifor iadolescents ientering ipubertyi. iThis istudy iaims ito idetermine ithe ieffect iof iadolescent ireproductive ihealth icounselling ion ithe ilevel iof iexpertise iin ifacing ipuberty iin ifemale istudents iat iIslamic iSchool iMiftahul iUlum iSilo iJember. iPre-iexperimental iresearch idesign iwith ione igroup iprei-itest iand iposti-itest idesign. iThe ipopulation iof iall iclass iVII istudents iis i29i, iwith inoni-iprobability isampling itechniquesi—idata ianalysis iwith iWilcoxon istatistical itesti. iBased ion ithe iresults iof ithe iWilcoxon itesti, ia ivalue iof < α (0.000<0.05) iwas iobtainedi. iThe ilevel iof iknowledge ibefore icounselling i (pre-test) iis ialmost ientirely (93.1%) iinsufficient iknowledge, iand iafter ibeing igiven icounselling i (post-test),imost (55.2%) ihave ia igood iunderstanding. iThe iresults iof ithis istudy ican ibe iconcluded ithat iadolescent ireproductive ihealth icounselling iinfluences ithe ilevel iof iknowledge iin ifacing ipuberty. iIt iis ihoped ithat ithe irespondents iof ithis istudy ican ihelp iincrease ithe iunderstanding iof ifemale istudents ifacing ipuberty.